Sustentabilidade e a questão urbana ambiental: o setor confeccionista de Divinópolis - Nogueira, Maria de Lourdes Couto (2016)
This thesis approaches the urban environmental question related to inadequate destination of textile solid residues originating from Divinópolis’ clothing manufacturers, pole city of confection. One of the goals is to get to know the city’s environmental scenario related to garment making industries, identifying their social acting people and their responsibilities concerning respect to the generation and disposal of the solid residues from this economic sector, being the ultimate purpose to contribute to the protection and preservation of the environment. Some items were collected for analysis data concerning the clothing companies from Divinópolis, as well as the positioning of the interviewed agents from the social role played by them in the environmental scenario of Divinópolis, having as study object the textile solid residues originating from the garment making industries. The main outcome obtained from the data analysis refers to the needs of environmental education and joint actions with every agent involved on the urban environmental issue of Divinópolis. Structured in four chapters, the thesis starts contextualizing the city and the Minas Gerais state on economic, social and environmental national scenario, as well as it introduces the appearance of the garment making sector, clothing manufacturer industries and their peculiarity. It discusses the urban environmental question, the solid waste, the pertinent legislation and the city as production space, consumption and disposal of solid waste. It also treats the administration and management of textile solid residues on the pole clothing manufacturer of Divinópolis, the alternatives for the final disposal of solid wastes and the environmental projets existing on Divinópolis. At last, it contextualizes the garment making sector on the environmental scenario of Divinópolis, presenting Divinópolis’ clothing manufacturer industries and their specificities, as well as the perceptions of the research’s participants’ positions in its peculiarities, similarities, differences, comparisons, among other aspects